The Essential of Using Standard Marine Communication Phrases in Avoiding Accidents at Sea for Indonesian Seafarers - haryani, Haryani; Januarius Mujiyanto; Rudi Hartono; Issy Yuliasri (International Journal of Education, Vocational and Social Science, 2023)
Standard Marine Communication Phrase (SMCP) is compulsory to be used onboard vessels by all seafarers worldwide, and it has been mandatory by International Maritime Organization (IMO). This research employs a qualitative method, and collecting the data is done by SMCP documents analysis in the context of onboard and external communication, administering open-ended questionnaires, conducting interviews, and recording. From the study, the usage of SMCP for external & internal communication had different numbers. The utilization of SMCP for external communication is 9% optional, 26% for recommend, and 65% mandatory. Moreover, the usage of English in crew radio communication, especially for onboard communication, differs in number. 11% of respondents chose optionally, 41% chose recommended, and 48% chose mandatory. From the finding, it could be summarized that Standard Marine Communication Phrase (SMCP) was rarely used by Indonesian seafarers while working on the bridge. They were reluctant to use the language for some reasons; the crew being fully Indonesian seafarers, lacked awareness of the language and never had any reward or punishment for the one who obeyed/disobeyed the regulation. Besides, they had to memorize every word from the standardized phrases from the SMCP book. Therefore, using SMCP for internal and external onboard communication has become the most crucial priority to avoid accidents and incidents at sea.